SINTESIS DAN KARAKTERISASI POLIMER BERCETAKAN MOLEKUL TARTRAZIN UNTUK PEMISAHAN WARNA TARTRAZIN PADA KERUPUK - Junita Br Sembiring (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
Tartrazine (E102) is a synthetic food dye that imparts a bright lemon-yellow coloration. The compound is composed of phenolic derivatives, polycyclic hydrocarbons, and heterocyclic structures. Its extensive application in the food sector is attributed to its remarkable stability against light, oxygen, heat, and pH variations, along with its relatively low production cost. In Indonesia, the National Agency of Drug and Food Control (BPOM) authorizes the use of tartrazine at a maximum concentration of 70 mg/kg in food and beverage products. However, excessive consumption may trigger adverse health effects such as allergic responses, skin irritation, migraines, and visual disturbances. Detection of tartrazine using molecularly imprinted polymers (MIPs) offers greater selectivity and precision compared to conventional analytical techniques. In this work, MIP was synthesized employing methacrylic acid (MAA) as the functional monomer, tartrazine as the template molecule, trimethylolpropane trimethacrylate (TRIM) as the crosslinking agent, benzoyl peroxide (BPO) as the radical initiator, and dimethylformamide as the porogenic solvent. The synthesized polymer was evaluated alongside a non-imprinted polymer (NIP) and characterized through FTIR, TGA, and SEM analyses. FTIR spectra revealed absorption bands at 1149.57 cm⁻¹, 1732.08 cm⁻¹, 2966.52 cm⁻¹, and 3441.01 cm⁻¹, corresponding respectively to C–H bending, carboxylate C=O stretching, C–H stretching, and O–H vibrations. The research results showed that a sample of crackers sold in a shop in the city of Bandung contained 0.42 mg/g or the equivalent of 420 mg/kg with a recovery of 95.47%.